Edukasi Deteksi Pencegahan Kanker Leher Rahim Melalui Vaksinasi HPV di SMAN 8 Kota Pekanbaru - Syamsul Bahri; Mofrilindo Mofrilindo; Erick Caesarrani; Ami Amelia; Yessi Rahayu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Cervical Cancer (Cervical Cancer) is a malignant tumor that grows in the cervix (the lowest part of the uterus that attaches to the top of the vagina. Cervical cancer usually attacks women aged 35-55 years. 90% of cervical cancer comes from squamous cells that lining the cervix and the remaining 10% comes from mucus-producing gland cells in the cervical canal that leads to the uterus. The aim of this activity is to prevent cervical cancer by providing outreach or education about The importance of HPV (Human Papilloma Virus) immunization in preventing the occurrence of cervical cancer so that preventive measures can be carried out as early as possible, so that it can reduce the incidence of cervical cancer. The result of this activity is to prevent the occurrence of cervical cancer Early prevention by carrying out HPV immunization